2021
DOI: 10.3390/ijerph18094638
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oral Contraceptives as a Potential Risk Factor for Breast Cancer: A Systematic Review and Meta-Analysis of Case-Control Studies Up to 2010

Abstract: Despite numerous studies evaluating the risk of breast cancer among oral contraception users, the effect of oral contraceptive on developing breast cancer remains inconclusive. Therefore, we conducted a systematic review of literature with meta-analysis in order to quantitative estimate this association. The bibliographic database MEDLINE and EMBASE, and reference lists of identified articles were searched, with no language restrictions, from the start of publication to August 2010. We performed a reanalysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 106 publications
0
18
0
5
Order By: Relevance
“…Here, IRR (incidence rate ratio) = 1.04, 95% CI: 0.91 to 1.17 [ 70 ]. Our previous meta-analysis covering the period 1960–2010 [ 16 ] estimated 79 case-control studies conducted between 1960–2010, including a total of 72,030 incidents, histologically confirmed cases of BrCa and 123,650 population/hospital controls. A decrease was observed in cancer risk in OC users before age 25 years (0.91, 0.83–1.00).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, IRR (incidence rate ratio) = 1.04, 95% CI: 0.91 to 1.17 [ 70 ]. Our previous meta-analysis covering the period 1960–2010 [ 16 ] estimated 79 case-control studies conducted between 1960–2010, including a total of 72,030 incidents, histologically confirmed cases of BrCa and 123,650 population/hospital controls. A decrease was observed in cancer risk in OC users before age 25 years (0.91, 0.83–1.00).…”
Section: Discussionmentioning
confidence: 99%
“…Pooled crude odds ratios of BrCa in ever-users of OC was 1.01 [95% confidence interval (CI), 0.95–1.07], compared with never-users. There was no significant increase in risk among premenopausal women (1.06, 0.92–1.22), postmenopausal women (0.99, 0.89–1.10), or nulliparous women (1.02, 0.82–1.26) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For gynecological problems, such as endometriosis and dysmenorrhea, it is recommended to consider whether there is a need for contraceptive medication, along with contraindications to hormonal therapy, and potential adverse effects [ 51 ]. Previous research indicated that knowledge of the risk factors of the medication is usually greater than of the beneficial effects, such as a reduced likelihood of contracting gynecological cancers, or other hormonal alterations [ 52 , 53 ]. In general, concerns about the consequences were the main factor involved in OCP definitive default.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between oral contraceptive (OC) taking and the risk of breast cancer has also been extensively researched. Findings suggest that OC use is associated with a moderately increased breast cancer risk in the general population [32][33][34][35].…”
Section: Introductionmentioning
confidence: 94%